3D chrysanthemum-like g-C3N4/TiO2 as an efficient visible-light-driven Z-scheme hybrid photocatalyst for tetracycline degradation. Issue 5 (16th January 2023) - Yu, Jia; Zhang, Chuanxiang; Yang, Yulin; Su, Ting; Yi, Guiyun; Zhang, Xiuxiu
Abstract : 3D chrysanthemum-like g-C3 N4 /TiO2 with a Z-scheme heterostructure is prepared via an in situ hydrothermal method and shows remarkable degradation performance toward tetracycline. Abstract : Utilization of a solar-driven semiconductor as a photocatalyst to degrade antibiotic pollutants is a feasible and environmentally friendly technology. In this paper, 3D chrysanthemum-like g-C3 N4 /TiO2 as a visible-light-driven hybrid photocatalyst with a Z-scheme heterostructure was firstly synthesized by the in situ hydrothermal synthesis method. Experiments proved that this 3D chrysanthemum-like g-C3 N4 /TiO2 had better degradation performance toward tetracycline than TiO2 and g-C3 N4 . In particular, when optimized g-C3 N4 /TiO2 -2 was applied for tetracycline removal (200 ml, 10 mg L −1 ), the corresponding degradation efficiency could reach nearly 100% within 60 min. The improved photocatalytic activity was the result of better utilization of the heterostructure-induced visible light, more efficient charge transfer in the Z-scheme heterojunction as well as stronger redox capability. The Z-scheme degradation mechanism was supported by the trapping experiments of active species and ESR radical detection, and the whole photocatalytic process was controlled by the combined action of ˙O2 −, h + and ˙OH radicals. This study may be beneficial for the design of more efficient sunlight-driven hybrid photocatalysts and their applications in wastewater treatment.